Transcription elements AREB6 and miR-34a affect apoptosis of PAMs by regulating the expression of SS2-related gene PPP1R11 - Guisheng Liu (2019)
© 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group. In our previous work, gene PPP1R11 (protein phosphatase 1 regulatory subunit 11) was significantly expressed in pigs after Streptococcus suis 2 (SS2) challenged. This study firstly confirmed that SS2 induced significant expression of PPP1R11 gene in porcine alveolar macrophage (PAM) cells, and apoptosis of PAM cells were observed. After that, the core promoter of porcine PPP1R11 was identified and its transcription factor AREB6 which significantly regulated PPP1R11. We also characterized that the PPP1R11 gene is a target of miR-34a. Further, we found that PPP1R11 helped to inhibit apoptosis of PAM cells under SS2 infecting, through transcription factor AREB6 was negatively correlated with apoptosis whereas miR-34a was positively correlated. Those findings provide a functional connection among the transcription factor AREB6, miR-34a, PPP1R11 gene and apoptosis of PAM cells in the pathogenesis of the SS2 infection.